2017
DOI: 10.1002/mc.22656
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated miR‐132 in Lgr5+ gastric cancer stem cell‐like cells contributes to cisplatin‐resistance via SIRT1/CREB/ABCG2 signaling pathway

Abstract: Cisplatin resistance has long been a major problem that restricts its use. A novel paradigm in tumor biology suggests that gastric tumor chemo-resistance is driven by gastric cancer stem cell-like (GCSCs). Growing evidence has indicated that microRNAs (miRNAs) contributes to chemo-resistance in gastric cancer (GC). Here, Lgr5 cells derived from gastric cancer cell lines displayed stem cell-like features. Flow cytometry demonstrated the presence of a variable fraction of Lgr5 in 19 out of 20 GC specimens. By co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 37 publications
(54 reference statements)
5
63
0
Order By: Relevance
“…recently described an upregulation of miR‐501‐5p in GC cell lines and specimens from patients with GC, functioning as an activator of the Wnt/β‐catenin signaling pathway and enhancing the CSC‐phenotype. MiR‐132 has been also found to be upregulated in Lgr5 + GCSC‐like cells in GC specimens, in correlation with chemoresistance and worse survival . In vitro, miR‐132 promoted resistance to cisplatin through the inhibition of SIRT, which results in enhanced expression of the transporter ABCG2, previously identified in multidrug resistance .…”
Section: Gastric Cancer Stem Cellsmentioning
confidence: 89%
“…recently described an upregulation of miR‐501‐5p in GC cell lines and specimens from patients with GC, functioning as an activator of the Wnt/β‐catenin signaling pathway and enhancing the CSC‐phenotype. MiR‐132 has been also found to be upregulated in Lgr5 + GCSC‐like cells in GC specimens, in correlation with chemoresistance and worse survival . In vitro, miR‐132 promoted resistance to cisplatin through the inhibition of SIRT, which results in enhanced expression of the transporter ABCG2, previously identified in multidrug resistance .…”
Section: Gastric Cancer Stem Cellsmentioning
confidence: 89%
“…For example, it was seen that miR-132 enhanced cisplatin resistance in gastric cancer cells by targeting SIRT1 which regulates ABCG2 expression by promoting the de-acetylation of the transcription factor CREB (SIRT1/CREB/ABCG2 pathway). Moreover, Kaplan-Meier survival analysis showed that low miR-132 is related to longer survival in chemo resistant gastric cancer [206] . Another example is Wnt/β-catenin-ABCG2 pathway, which is modulated by miR-199a/b in colorectal cancer stem cells, and whose upregulation is related to cisplatin resistance [207] .…”
Section: Abcg2 Inhibitorsmentioning
confidence: 99%
“…Use of microRNA has revealed a more complex role of ABCG2 in drug resistance related signaling pathways: SIRT1/CREB/ABCG2 and Wnt/β-catenin-ABCG2 pathway Breast, ovarian cancer, other cell lines [200][201][202][203][204][205][206][207] TKI: tyrosine kinase inhibitor; MDR: multidrug resistance; CML: chronic myeloid leukemia; NSCLC: non-small cell lung cancer their inhibition will also increase the oral bioavailability of the drug, in addition to its penetration to the tumor site. However, since these two transporters are also expressed in sanctuary sites, caution for potential toxic side effects should be considered.…”
Section: Dual Inhibitorsmentioning
confidence: 99%
“…The miR‐145 targeting of CD44 plays fundamental roles in the modulation of cancer growth and MDR in GC, and the miR‐129 targeting of P‐gp regulates DDP resistance in GC cells . Other miRNAs, such as miR‐132, miR‐524‐5p, miR‐34a, and miR‐200c (200–202) also promote resistance to DDP in GC. In a current study, miRNA‐132 was verified to promote cisplatin resistance in a GC stem cell‐like Lgr5 cells both in vitro and in vivo, which used to be mediated through the regulation of SIRT1/CREB/ABCG2 signaling pathway .…”
Section: Mirnas and Drug Resistance In Gcmentioning
confidence: 99%
“…Other miRNAs, such as miR‐132, miR‐524‐5p, miR‐34a, and miR‐200c (200–202) also promote resistance to DDP in GC. In a current study, miRNA‐132 was verified to promote cisplatin resistance in a GC stem cell‐like Lgr5 cells both in vitro and in vivo, which used to be mediated through the regulation of SIRT1/CREB/ABCG2 signaling pathway . The sensitivity of GC cells to cisplatin can enhance by a low expression level of miR‐99a and miR‐491 through targeting CAPNS1/calpain1/calpain2/caspase‐3/PARP1 signaling pathway directly …”
Section: Mirnas and Drug Resistance In Gcmentioning
confidence: 99%